Recent advances in different interactions between toll-like receptors and hepatitis B infection: a review - Soleiman-Meigooni, Saeed; Yarahmadi, Aref; Kheirkhah, Amir-Hossein; Afkhami, Hamed (Frontiers in Immunology, 2024)
Hepatitis B virus (HBV) B infections remain a primary global health concern. The immunopathology of the infection, specifically the interactions between HBV and the host immune system, remains somewhat unknown. It has been discovered that innate immune reactions are vital in eliminating HBV. Toll-like receptors (TLRs) are an essential category of proteins that detect pathogen-associated molecular patterns (PAMPs). They begin pathways of intracellular signals to stimulate pro-inflammatory and anti-inflammatory cytokines, thus forming adaptive immune reactions. HBV TLRs include TLR2, TLR3, TLR4, TLR7 and TLR9. Each TLR has its particular molecule to recognize; various TLRs impact HBV and play distinct roles in the pathogenesis of the disease. TLR gene polymorphisms may have an advantageous or disadvantageous efficacy on HBV infection, and some single nucleotide polymorphisms (SNPs) can influence the progression or prognosis of infection. Additionally, it has been discovered that similar SNPs in TLR genes might have varied effects on distinct populations due to stress, diet, and external physical variables.In addition, activation of TLR-interceded signaling pathways could suppress HBV replication and increase HBV-particular T-cell and B-cell reactions. By identifying these associated polymorphisms, we can efficiently advance the immune efficacy of vaccines. Additionally, this will enhance our capability to forecast the danger of HBV infection or the threat of dependent liver disease development via several TLR SNPs, thus playing a role in the inhibition, monitoring, and even treatment guidance for HBV infection. This review will show TLR polymorphisms, their influence on TLR signaling, and their associations with HBV diseases.